2005
DOI: 10.1007/s10633-005-0653-3
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependency and Time-course of Electrophysiologic Short-term Effects of VIAGRA®: A Case Study

Abstract: The dose-dependency and time-course of the short-term visual effects of sildenafil citrate (VIAGRA) were tested in two subjects. Blood pressure was measured and samples of blood taken at 30 min intervals before and after drug administration. In the first experiment, prolongations of the implicit times of the scotopic maximum a-wave, cone a- and b-wave, 33 Hz flicker, ON-response a- and b-wave and 3.3 Hz a- and b-wave electroretinogram (ERG) recordings and of the oscillatory potentials OP1, OP2, and OP3 were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[29][30][31][32] The most consistent finding has been a reversible prolongation of b-wave implicit time in the cones (rods may be affected also). 29 This is evident in both full-field and multifocal ERG, and in the a-wave of the dark-adapted combined standard response.…”
Section: Resultsmentioning
confidence: 95%
“…[29][30][31][32] The most consistent finding has been a reversible prolongation of b-wave implicit time in the cones (rods may be affected also). 29 This is evident in both full-field and multifocal ERG, and in the a-wave of the dark-adapted combined standard response.…”
Section: Resultsmentioning
confidence: 95%
“…PDE-6 is a critical regulator of the photoreceptor transduction cascade. Human ERG studies have shown mild and somewhat variable reductions in full-field and mfERG amplitude in subjects after a single, large dose of sildenafil [4][5][6]. The most consistent finding has been a modest increase in cone b-wave implicit time.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent finding has been a modest increase in cone b-wave implicit time. Oscillatory potentials may be delayed as well [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations